2022
DOI: 10.1186/s13148-022-01285-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of ovarian cancer using plasma cell-free DNA methylomes

Abstract: Background Ovarian cancer (OC) is a highly lethal gynecologic cancer, and it is hard to diagnose at an early stage. Clinically, there are no ovarian cancer-specific markers for early detection. Here, we demonstrate the use of cell-free DNA (cfDNA) methylomes to detect ovarian cancer, especially the early-stage OC. Experimental design Plasma from 74 epithelial ovarian cancer patients, 86 healthy volunteers, and 20 patients with benign pelvic masses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Antioxidants have the power to reduce its severity. That is why they are told to eat nutritious natural vegetables and fruits [21].…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants have the power to reduce its severity. That is why they are told to eat nutritious natural vegetables and fruits [21].…”
Section: Introductionmentioning
confidence: 99%
“…We also analyzed whether miR-139-5p and miR-451a in early patients have similar diagnostic values in late patients. We found that the early model had weak diagnostic ability for patients with late patients, 29 indicating that early markers can be roughly presented in each stage of LUSC. However, this result confirms that early-stage markers can generally present the molecular characteristics of LUSC in all stages.…”
Section: Dovepressmentioning
confidence: 78%
“…The use of this approach is spreading in cancer studies (4)(5)(6)(7)(8). Direct detection of altered DNA methylation patterns under pathological conditions, regardless of cell or tissue contribution, has been thoroughly examined to determine its value as a strategy for searching for biomarkers (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%